THE PREVALENCE OF DIABETIC RETINOPATHY - Fitriani Fitriani; Aslim D Sihotang; Delfi Delfi (Jurnal Kesehatan Prima, 2017)
Diabetic Retinopathy is a damage retina caused by complication of diabetes mellitus. Approximately 40% of the diabetes cases tend to be retinopathy diabetic, even 8% of those cases are going to have blindness. The research aimed to describe diabetic retinopathy prevalence at H Adam Malik Hospital in Medan. The research method was retrospective descriptive and samples ware acquired from medical record during July in 2011 to June in 2012 at H Adam Malik Hospital in Medan. The findings indicated that there was no significant difference of a number of diabetic retinopathy patients between man and women. Mostly diabetic retinopathy patients were approximately 50 – 59 years old with duration of diabetes mellitus for 5 to 10 years old. The conclusion is the height of prevalence diabetic retinopathy is influenced by age and duration of diabetes mellitus.